Fuzzy Stabilization of Power Systems in a Co-Generation Scheme Subject to Random Abrupt Variations of Operating Conditions - Arrifano, N.S.D.; Oliveira, V.A.; Ramos, R.A.; Bretas, N.G.; Oliveira, R.V. (IEEE transactions on control systems technology, 2007)
In this brief, a new stabilizing controller for the power system of an industrial plant operating in a co-generation scheme is proposed. The main source of perturbations considered in the operating conditions are random abrupt fluctuations in the local load, corresponding to the industrial processes being turned on and/or off. These fluctuations are described as Markovian jumps in the parameters of the power system. The proposed controller follows a standard structure which combines an automatic voltage regulator with a supplementary stabilizing term. This term is obtained with a fuzzy-model-based control technique formulated in the context of linear matrix inequalities under damping and control input constraints. Simulations performed on both a single-machine infinite-bus model and on a multimachine model show the effectiveness of the proposed fuzzy control strategy in reducing the oscillations as well as in maintaining a desired operating condition